2023
DOI: 10.3390/nu15214639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regular Consumption of a Miraculin-Based Food Supplement on Taste Perception and Nutritional Status in Malnourished Cancer Patients: A Triple-Blind, Randomized, Placebo-Controlled Clinical Trial-CLINMIR Pilot Protocol

Bricia López-Plaza,
Ángel Gil,
Adrián Menéndez-Rey
et al.

Abstract: Taste disorders are common among cancer patients undergoing chemotherapy, with a prevalence ranging from 20% to 86%, persisting throughout treatment. This condition leads to reduced food consumption, increasing the risk of malnutrition. Malnutrition is associated not only with worse treatment efficacy and poor disease prognosis but also with reduced functional status and quality of life. The fruit of Synsepalum dulcificum (Daniell), commonly known as miracle berry or miracle fruit, contains miraculin, a taste-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 162 publications
0
7
0
Order By: Relevance
“…Recently, we reported that regular consumption of DMB improved energy intake, fat quantity and quality, fat-free mass, and quality of life in malnourished cancer patients receiving antineoplastic treatment (16). Considering these results, a logical approach is to discern whether this improvement is reflected in the cachexia status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we reported that regular consumption of DMB improved energy intake, fat quantity and quality, fat-free mass, and quality of life in malnourished cancer patients receiving antineoplastic treatment (16). Considering these results, a logical approach is to discern whether this improvement is reflected in the cachexia status.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot CLINMIR study was designed to evaluate the efficacy and safety of the DMB food supplement on sensory function, nutritional status, dietary intake, quality of life and the fatty acid profile of erythrocytes in adult malnourished cancer patients with taste disorders undergoing active antineoplastic therapy (17). The complete protocol as well as the results of the major characteristics of patients and main outcomes, as well as the DMB composition, have been reported elsewhere (16,17).…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the CLINMIR study protocol has recently been published elsewhere [ 40 ]. Below is a summary of the clinical trial.…”
Section: Methodsmentioning
confidence: 99%